Knowledge, perceptions and attitude of community members and healthcare workers regarding the donation of breast milk and use of donated human milk (DHM) in Empangeni, KwaZulu-Natal - Govender, Nicole (Department of Paediatrics and Child Health, 2021)
Background: Breast milk provides optimal nutrition for infants. Human milk banks allow breast milk feeding for infants who do not have access to their own mother's milk. However, there are variable perceptions and attitudes towards human milk banking. Aim: This study aimed to evaluate community members' and healthcare workers' knowledge, perceptions and attitudes towards breast milk donation and use in Empangeni, KZN. Methodology: The research was conducted at a large regional hospital and an affiliated primary health care centre in the area. There were five focus group discussions held with healthcare workers employed at the two sites which explored the attitudes regarding donating and receiving breast milk. In addition, there were sixteen individual semi-structured interviews held with community members. Content analysis was used to analyse the data. Results and Discussion: Five main themes were found which includes: “Breastfeeding is an optimal feeding choice”, “Infant feeding choice”, “Misperceptions of HIV”, “Knowledge of DHM” and “Acceptance of DHM”. Though most participants were aware of breastfeeding benefits, there are poor breastfeeding rates within the area. Many mothers choose to formula feed their infants due to the fear of HIV transmission. There is also a fear of HIV transmission when using DHM. Acceptance of DHM was largely related to knowledge of DHM and exposure to its use. Conclusion: Healthcare workers need to be given updated, evidence-based information (in accordance with national guidelines and policies) to ensure appropriate counselling of caregivers. Furthermore, community awareness and engagement is required to improve breastfeeding rates and acceptability of DHM.